Characterization of Photosystem I in the Red Alga Porphyridium purpureum - Kosmas, Panagiotis (Jihočeská univerzita, 2020)
Photosynthesis, a fundamental biochemical process on planet Earth, has passed through several steps during the course of evolution since beginning of time. Red algae represent a primitive stage of evolution of photosynthesis in eukaryotes, hence they are important for our understanding of functioning and evolution of photosynthetic energy conversion in general. In the current work, isolation and characterization of the supramolecular complex consisting of photosystem I with three antenna complexes from the red alga Porphyridium purpureum is presented. The purification consisted of sucrose gradient centrifugation followed by anion exchange and size-exclusion chromatography. The composition of the PSI-antenna supercomplex was confirmed using electrophoresis and reverse-phase chromatography. Function of the isolated supercomplex was further investigated using time-resolved absorption and fluorescence spectroscopy.
Characterization of Photosystem I in the Red Alga Porphyridium purpureum
Keywords: chlorophyll a; phycobilisomes; sucrose band; SDS-gel page; psaA; D1/D2 proteins; Light Harvesting Complex; porphyridium purpureum; nannochloropsis oceanica; fluorescence spectroscopy; carotenoids; chromatography; chloroplasts; centrifugation; fractionation.